Research in personnel and human resources management. Vol. 20 - Ferris, Gina. (Bingley, U.K. : Emerald, 2001)
This volume is part of a series which publishes monograph length conceptual papers designed to promote theory and research on important substantive and methodological topics in the field of human resources management.
Overview / Gerald R. Ferris -- Three roads to organizational justice / Russell Cropanzano, Deborah E. Rupp, Carolyn J. Mohler, Marshall Schminke -- Establishing the dimensions, sources and value of job seekers' employer knowledge during recruitment / Daniel M. Cable, Daniel B. Turban -- The strategic management of people in work organizations : review, synthesis, and extension / John E. Delery, Jason D. Shaw -- Bringing variety and change into strategic human resource management research / Peter D. Sherer, Huseyin Leblebici -- National unions as organizations / Jack Fiorito, Paul Jarley, John T. Delaney -- Downsizing and organizational performance : a review of the literature from a stakeholder perspective / John Kammeyer-Mueller, Hui Liao, Richard D. Arvey -- Employee silence : quiescence and acquiescence as responses to perceived injustice / Craig C. Pinder, Karen P. Harlos -- Implications of the converging economy for human resource management / Suzanne Zivnuska, David J. Ketchen, Charles C. Snow.
Print version record
Keywords: Business & Economics -- Management; Science -- History; Personnel & human resources management; Personnel management